The library of isolated bacteria from gut microbiota in classical fish models: Zebrafish (Danio rerio), marine (Oryzias melastigma) and freshwater (Oryzias latipes) medaka - Lan-Chen Zhang; Yan Li; Ming-Fei Wu; Jin-Qiu Jia; Pan-Pan Jia (PLoS ONE, 2026)
Zebrafish ( Danio rerio ), Marine medaka ( Oryzias melastigma ), and freshwater medaka ( Oryzias latipes ) are three major animal species in evaluation of environmental pollutant toxicity and building of human disease models with conserved physiological and molecular pathways. Bacterial strains from gut microbiota should firstly be isolated for their functions’ exploration. In this study, we optimized a culture-based workflow under aerobic and anaerobic conditions to recover intestinal bacteria from adult zebrafish (ZF), marine medaka (MM), and freshwater medaka (OL) using both dissection-based and in vivo sampling. The isolates were then identified by Gram staining, 16S rRNA gene sequencing, phylogenetic analysis, and API 20E-based biochemical characterization. The culturable bacteria isolated from gut microbiota were identified belonged to 14 genera in ZF, 12 genera in MM, and 18 genera in OL. Comparative analysis showed clear differences in the composition of cultured gut bacteria among the three fish species. Overall, the library and the differences of gut bacteria in three key fish models provided the potential applications of bacterial strains as the probiotics, to against the fish pathogens and to increase the pollutant toxicity-resistant. Moreover, the bacterial library will support the deep researches combined with germ-free (GF) animals to clarify the relationships of intestinal microbiota to host health.